2015
DOI: 10.1111/tra.12304
|View full text |Cite
|
Sign up to set email alerts
|

GSK‐3β Phosphorylation of Cytoplasmic Dynein Reduces Ndel1 Binding to Intermediate Chains and Alters Dynein Motility

Abstract: Glycogen synthase kinase 3 (GSK‐3) has been linked to regulation of kinesin‐dependent axonal transport in squid and flies, and to indirect regulation of cytoplasmic dynein. We have now found evidence for direct regulation of dynein by mammalian GSK‐3β in both neurons and non‐neuronal cells. GSK‐3β coprecipitates with and phosphorylates mammalian dynein. Phosphorylation of dynein intermediate chain (IC) reduces its interaction with Ndel1, a protein that contributes to dynein force generation. Two conserved resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 75 publications
5
61
1
Order By: Relevance
“…Pharmacological inhibition of GSK3b in hippocampal and sensory (dorsal root ganglion, DRG) neurons has been shown to stimulate the axonal transport of brain-derived neurotrophic factor (BDNF)-containing secretory vesicles, mitochondria, and acidic organelles [24,28]. Similar results are also seen in Drosophila larval segmental nerves carrying loss-of-function mutations in GSK3 [27].…”
Section: Key Figurementioning
confidence: 79%
See 1 more Smart Citation
“…Pharmacological inhibition of GSK3b in hippocampal and sensory (dorsal root ganglion, DRG) neurons has been shown to stimulate the axonal transport of brain-derived neurotrophic factor (BDNF)-containing secretory vesicles, mitochondria, and acidic organelles [24,28]. Similar results are also seen in Drosophila larval segmental nerves carrying loss-of-function mutations in GSK3 [27].…”
Section: Key Figurementioning
confidence: 79%
“…These contrasting results may represent differences in the regulation of axonal transport between species. GSK3b directly phosphorylates dynein intermediate chain 1B (DIC1B) and 2C (DIC2C), leading to inhibition of the retrograde axonal transport of acidic organelles [28]. GSK3b-mediated phosphorylation of DIC1B was shown to reduce its interaction with Ndel1 and Lis1, which enhance dynein force production [31].…”
Section: Key Figurementioning
confidence: 99%
“…As Cdk5 and GSK3 kinases regulate Dynein 32,33 and because FEME carriers containing Shiga toxin rely on this microtubule motor for scission and retrograde trafficking 34,35 , a role for the kinases in regulating Dynein during FEME was explored. We confirmed that inhibiting Dynein (with either the small inhibitor Ciliobrevin D 36 or the overexpression of the p50 dynamitin subunit of the dynactin complex 37 ) blocked FEME carrier budding and β1AR endocytosis ( Supplementary Figure S5a-b ).…”
Section: Resultsmentioning
confidence: 99%
“…GSK-3β has been reported to phosphorylate dynein intermediate chain (IC) at S87/ T88 in IC-1B and S88/T89 in IC-2C, which are the key sites for NDEL1 binding domain, leading to reduction of its interacting with NDEL1 [26]. Thus, the interaction of NDEL1 and dynein is negatively regulated by GSK-3β.…”
Section: Gsk-3β Regulates Mitochondrial Motilitymentioning
confidence: 99%